Stredoveký meč z obce Bohdan Rakhivského rajónu Zakarpatskej oblasti Ukrajiny - Калініченко, Віталій; Прохненко, Ігор (Brno, Masarykova univerzita, 2015)
A sword dated to the second half of the 13th century – the beginning of the 14th century was accidentally found by local shepherd Yuriy Retyaznyk in September 2014 in the Nimychnyy cadastral zone, close to the village of Bohdan in the Rakhiv district of Zakarpats'ka oblast, Ukraine. This type of weapon is quite rare both in the Upper Tisza region and Central-Eastern Europe. Typological schemes of E. Oakeshott, M. Aleksić, A. Geibig, Z.-K. Pinter and M. Šercerova were used for its identification. Results of the analysis of the sword construction provided information for the assessment of the development of bladed weapons in the Middle Ages.
A medieval sword from the village of Bohdan in the Rakhiv district of Zakarpats'ka oblast, Ukraine
Ein mittelalterliches Schwert aus der ukrainischen Gemeinde Bohdan im Rajon Rakhiw der Oblast Transkarpatien
Keywords: Bohdan; bladed weapon; sword; blade; hilt; typology